A Review on the Role of Naladadi Ghrita (A Polyherbal Medicated Ghee) in the Management of Jarajanya Medhakshaya (Age Related Deterioration of Intellect) - M K, Mridula; Ansary, PY; Oommen, Sara Moncy; Shincymol, V V; R, Sethu (International Research Journal of Ayurveda & Yoga, 2022)
Ageing and related ailments especially mental health conditions imparts a greater burden in elderly population. Age related dementia including both memory loss and cognitive impairment is a leading contributor of disability. Due to the concern over safety of available pharmacological therapies many people with dementia turn to complementary medicine. Ayurveda, the Indian system of medicine recognises this condition as Medhakshaya (deterioration of intellect) and has given much emphasis on drugs which will promote Medha. Several rasayana drugs in ayurveda are primarily claimed as medhya since they have the ability of mental upliftment. Naladadi ghrita is such a formulation described in rasayana prakarana of Ashtanga hridaya and in this review we tried to analyse individual drug action and their synergetic action. Role of drugs in neuroprotection, learning and memory was analysed by electronic database search. And drugs were also reviewed by ayurveda parameters. Results of the review revealed the role of individual drugs in digestion and various brain functions. combination of drugs may produce an extra therapeutic effectiveness by synergism and can be utilised for the treatment of various CNS disorders including jarajanya medhakshaya.